Study of optimal layout based on integrated probabilistic framework (IPF): Case of a crude oil tank farm. (July 2017) - Zhang, Mingguang; Dou, Zhan; Liu, Longfei; Jiang, Juncheng; Mebarki, Ahmed; Ni, Lei
Abstract: This paper gives an integrated probabilistic framework (IPF) that deals with the optimal layout of facilities in an industrial plant. The specific case of a crude oil tank farm is detailed in this present paper, which includes the tank fire as well as the corresponding optimal layout based on inherent safety and evacuation. The tank fire can be caused by the oxidative self-heating of pyrophoric iron sulfides which extensively exist on the inner wall of the crude oil tank, especially in the respiratory/safety valves. Oxidative self-heating, or spontaneous combustion of iron sulfides is a process of oxidation and generally influenced by five external factors including water content, mass per unit area of iron sulfides, operating temperature of tank, flow rate and concentration of oxygen facing the iron sulfides. According to the previous literature about self-heating process of iron sulfides, the maximum temperature ( T m a x ) of solid phase is a vital indicator representing the pyrophoric feature of iron sulfides in specific circumstances. And the maximum temperature ( T m a x ) can be predicted by the model developed from support vector machine (SVM) technique. While the predicted maximum temperature ( T m a x ) is compared with a defined threshold value, it can be revealed whether the oxidative self-heating of iron sulfides will lead to explosion and then cause tank fire. On this grounds, the probability of tank fire due to the oxidative self-heating of iron sulfides can be obtained by Monte Carlo simulations. For tank fire, the major physical damage to the surrounding tanks and workers is thermal radiation rather than overpressure or missile projection. Considering the worst case scenario, that is the vapor-liquid interface in the tank covered with fire, then the thermal radiation flux passing through a receiver at a specified distance away from the tank can be derived. In reverse, the critical horizontal distance between tank and receiver can be obtained if the critical thermal radiation flux through a receiver is given. Assuming that the minimum and maximum risks of thermal radiation to a receiver are separately 0 and 1 corresponding to different thermal radiation fluxes, then the risk of a tank or worker receiving a given thermal radiation flux can be determined by the thermal radiation flux equation. In a crude oil tank farm containing more than one tank, the potential thermal radiation flux received by an object at an arbitrary location is the superposition of those from different tanks. For the optimization of space collocation and floor area of tank farm from inherently safe design, if the damage risk of an object from other overall tanks equals to the critical acceptable damage risk, and the corresponding floor area of tank farm is the minimum, it will certainly result in an optimal space collocation. The handling method for the mentioned problem inherently reduces property loss and casualty to some extent. Highlights: An integrated probabilistic framework is applied in the optimal layout of a crude oil tank farm. Probability of an initiating event due to self-heating of iron sulfides is determined. Equation deduced to calculate thermal radiation flux is given. Lumped damage risk method is developed and confirmed. Application of lumped damage risk in the optimal layout of a crude oil tank farm certificates its highly effectiveness.